Analisis Efektivitas Pengawasan dalam Penyelenggaraan Tata Kelola Pemerintahan Kabupaten Pangandaran - Putri Aksa Yemima; Ester Yulianti Pakpahan; Muhammad Mifftah Fauzan; Thalia Oktaviana Adianto; Ivan Darmawan (Lembaga Pengembangan Kinerja Dosen, 2024)
Supervision in regional government governance is very important to create effective, efficient and transparent government. Pangandaran District faces major challenges in supervision, including low transparency, community participation, misalignment of program planning and implementation, and low accountability. This research analyzes the effectiveness of supervision in Pangandaran, identifying obstacles, and providing recommendations for improvement. Using qualitative methods and literature studies, the research results show the need for increased transparency, community participation, harmonized planning and accountability. Implementation of these recommendations is expected to improve government governance and increase public trust.